Small Wild Felids of South America: A Review of Studies, Conservation Threats, and Research Needs - Moreira-Arce, D (Springer International Publishing, 2023)
A total of nine small wild felid species can be found in a diversity of habitats in South America. Hierarchical models (HM) can be used to estimate key population aspects such as their distribution, abundance, density, and the influence of environmental conditions. The HM framework can accommodate errors introduced during the observation process, separating them from the ecological process that is key to informing conservation actions. In this chapter, we review studies on small wild felids of South America that estimate abundance, density, and occupancy using HM. We quantify the number of studies per species and ecoregions, as well as assess survey effort, parameter estimates, and their precision. We also qualitatively summarize conservation recommendations arrived at directly from HM results. Based on a priori inclusion criteria, we reviewed 81 studies published between 2002 and 2022. The most widely used detection method was camera-trapping. By 2015, occupancy studies had surpassed those of density and abundance in terms of the relative number of publications. The species with the highest number of studies was the ocelot (Leopardus pardalis; n = 49), and the ones with the least were the Andean cat (L. jacobita) and southern tigrina (L. guttulus) (n = 3 each). L. pardalis also dominated HM application in terms of cumulative survey effort (>2 million trap nights). The ocelot showed the broadest range of density estimates and SE values on density and occupancy. The low precision of model estimates but relatively large survey effort for some species suggests the need for more species-specific survey designs (e.g., H. yagouaroundi and L. wiedii). Conservation recommendations based on the results of HM studies suggest mitigating impacts in three main dimensions: habitat degradation, direct human pressures, and impacts of both native and domestic carnivores. Priority use of HM should be given to species such as Herpailurus yagouaroundi, L. guttulus, L. colocolo complex, and L. jacobita, as well as geographical areas for which there are research gaps in demographic parameters. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2023. All rights reserved.